GIS-based study of the evolution of the IGN's strong motion network of mainland Spain and the balearics - Amaro-Mellado, José-Lázaro; Antón, Daniel; Alcalde, Juan-Manuel (KeAi Communications Co., 2022)
In some countries with seismicity, an adequate detection network is essential to assess seismic hazards. The Instituto Geográfico Nacional (National Geographic Institute/IGN) of Spain manages a strong motion network distributed throughout the whole country and an earthquake detection network composed of velocity stations. This paper aims at studying the development of the strong motion network of the Spanish National Seismic Network (focusing on mainland Spain and the Balearics) in the last three decades. A Geographic Information System (GIS) has been implemented to integrate the attributes from the IGN's database concerning the earthquake catalogue, seismograph and accelerometer networks, which enabled to analyse the data and map the distribution of detection equipments in the region. The irregularly distributed Spanish strong motion network was greatly expanded from 1990 to 2010. In the past decade, it developed at a slower rate, but more modern technology was implemented.
Keywords: accelerometer network; earthquake catalogue; GIS; spanish national seismic network; strong motion; Scopus; Emerging